UPAYA PENINGKATAN BACA TULIS AL-QURAN MELALUI METODE QIROATI - Defy Habibi Muhammad (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2018)
This study used a qualitative approach and descriptive type of research, with the aim to provide a snapshot of a particular symptom. Techniques of data collection through observation, interviews, documentation and snowballing sampling. To analyze the data used descriptive qualitative methods and triangulation, the description is based on the symptoms that appear while the triangulation, ie, data checking technique that uses something other than the data for checking purposes or as a comparison to the data. The source of the data used in this research is the source of primary data and secondary data sources. This research used theory which is a method Glann calistung Doman. From the results ofthis study indicate that individuals Village Jati Probolinggo qiroati considers that this method is a method that is appropriate to in crease the reading and writing of the Qur'an as it is a method of reading the Qur’an that directly incorporate and practice reading Tartil accordance with qoidah tajwid. Effectiveuse of methods qiroati, qiroati method can be implemented by way of grouping students according to the level of its volumes since this method does not see the age of the child but the child's ability malihat. Cooperation between the agencies and parents to develop and increase interest in reading and writing of the Qur'an to his son. Ustadz/ustdzah trying to improve the reading and writing of the Qur'an by using classical methods of individual and under stand each students individual differences.